2009
DOI: 10.1007/s00374-009-0354-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between N mineralization or microbial biomass N with micromorphological properties in beech forest soils with different texture and pH

Abstract: To test relationships between net N-mineralization, organic matter and soil organisms, we combined micromorphology with laboratory incubation experiments over a soil gradient. Microbial biomass N generally increased with pH, and from sandy to loamy soil, but net N-mineralization showed the opposite, and was highest in acid, sandy soil. Twenty-two micromorphological characteristics were analyzed with principal component analysis. PC1 had high eigenvalue (0.70), and clearly separated fungi from earthworms, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 45 publications
0
30
1
Order By: Relevance
“…In contrast, some other research has found that these invertebrates prefer a lower pH, which is favourable for the development of fungi, the food source for other soil invertebrates which in turn form the prey for mesostigmatids (Chikoski et al 2006;Manu 2011a;Birkhofer et al 2012). Acidity and dominance of sandy soils (such as those described from the six grassland ecosystems in the present study) are known to contribute to low actinomycete biomass (Kooijman et al 2009;Birkhofer et al 2012).…”
Section: Discussioncontrasting
confidence: 68%
“…In contrast, some other research has found that these invertebrates prefer a lower pH, which is favourable for the development of fungi, the food source for other soil invertebrates which in turn form the prey for mesostigmatids (Chikoski et al 2006;Manu 2011a;Birkhofer et al 2012). Acidity and dominance of sandy soils (such as those described from the six grassland ecosystems in the present study) are known to contribute to low actinomycete biomass (Kooijman et al 2009;Birkhofer et al 2012).…”
Section: Discussioncontrasting
confidence: 68%
“…These observations of decreased P availability are in contrast to effects of CO 2 fumigations at other soil types (Ebersberger et al 2003;Khan et al 2008). The sensitivity in soil P availability to enhanced CO 2 might, however, be soil specific and related to soil pH, contents of ion, aluminum and other adsorbing minerals important for soil P chemistry (Britton et al 2003;Chapin III et al 2002;Kooijman et al 2009). In studies with shortterm treatments, pulse releases of P after drying and rewetting of soils were observed but with no relation to microbial biomass C (Blackwell et al 2009;Butterly et al 2009).…”
Section: Decreased Phosphorus Availability Under Elevated Comentioning
confidence: 88%
“…In terrestrial soils, increase in net N-mineralization from high to low pH seemed associated with a shift in microbial community (Kooijman et al 2008(Kooijman et al , 2009). Bacteria usually predominate at high pH, and fungi under more acid conditions (Bååth and Anderson 2003).…”
Section: Low Instead Of High Nutrient Availability In Calcareous Fensmentioning
confidence: 99%